The impact of dehydration and extremely low HCl values in the Antarctic stratospheric vortex in mid-winter on ozone loss in spring - Zhang-Liu, Yiran; Müller, Rolf; Grooß, Jens-Uwe; Robrecht, Sabine; Vogel, Bärbel; Zafar, Abdul Mannan; Lehmann, Ralph (EGU, 2024)
Simulations of Antarctic chlorine and ozone chemistry in previous work show that in the core of theAntarctic vortex (16–18 km, 85–55 hPa, 390–430 K) HCl null cycles (initiated by reactions of Cl with CH4 andCH2O) are effective. These HCl null cycles cause both HCl molar mixing ratios to remain very low throughoutAntarctic winter and spring. They cause ozone-destroying chlorine (ClOx ) to remain enhanced so that rapidozone depletion proceeds. Here we investigate the impact of the observed dehydration in Antarctica, whichstrongly reduces ice formation and the uptake of HNO3 from the gas phase; however the efﬁcacy of HCl nullcycles is not affected. Moreover, also when using the observed very low HCl molar mixing ratios in Antarcticwinter as an initial value, HCl null cycles are efﬁcient in maintaining low HCl (and high ClOx ) throughout winterand spring. Further, the reaction CH3O2 + ClO is important for the efﬁcacy of the HCl null cycle initiated by thereaction CH4 +Cl. Using the current kinetic recommendations instead of earlier ones has very little impact on thesimulations. All simulations presented here for the core of the Antarctic vortex show extremely low minimumozone values (below 50 ppb) in late September to early October in agreement with observations.